The Miqqut project: Joining literacy, culture and well-being through non-formal learning in Nunavut - Tulloch, Shelley; Pilakapsi, Quluaq; Uluqsi, Gloria; Kusugak, Adriana; Chenier, Cayla; Crockatt, Kim (Ilitaqsiniq - Nunavut Literacy Council, 2013)
This research documents the outcomes of non-formal traditional skills programs with embedded literacy. A community-based research team conducted one hundred interviews with participants and instructors of five non-formal cultural programs offered in Rankin Inlet, Nunavut. Four of the five programs focused on sewing and related practices of fur preparation, pattern creation, and esthetic design. The fifth program targeted fine arts ranging from drawing to ceramics. Each program embedded literacy to varying degrees. Two of the programs also targeted personal well-being. Systematic analysis of instructor and participant testimonies reveals concurrent cultural, literacy and wellbeing outcomes in all five programs. Participants’ and instructors’ testimonies show how culture, literacy and well-being overlap for strong impact in participants’ lives. Ilitaqsiniq’s research confirms that non-formal cultural programs with embedded literacy are effective venues for literacy and essential skills development. Furthermore, such programs help participants develop as resilient individuals, contributing to stronger families and communities.